The methodical approach to account of threshold meanings of indicators for the analysis of energy safety on an example Moldavian Power System - Bicova E.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2003)
The new method of account of threshold meanings of indicators of energy security- method of functional interrelations is described which allows to take into account mutual communication of indicators of energy safety ss among themselves, and with indicators of economic safety. It enables on the accepted one main threshold meaning of the indicator of economic safety with use of the block diagrams of interrelation to expect threshold meanings of indicators of energy safety. The indicators of energy safety is chosen and systematized in blocks. Tine results of accounts of indicators of energy safety - threshold and actual are given, and on them the estimation of a condition of a level of energy safety of power system of Moldova is made.